The Right To Be Heard And The Imposition Of Restriction Orders Under The Internal Security Act - Nijar, Gurdial Singh (Journal of Malaysian and Comparative Law, 2018)
The Right To Be Heard And The Imposition Of Restriction Orders Under The Internal Security Act